The Impact of the Implementation of the Independent Teaching Platform on Teachers' Pedagogical Competence - Puja, Sahara; Ayu Ningrum, Tia; Nellitawati; Hayati, Nikmah (Journal of Educational Management Research, 2025)
This study aims to investigate the impact of implementing the Merdeka Mengajar (PMM) Platform on teachers' pedagogical competence. This study employed a quantitative method with a causal-associative research design. The study population consisted of 202 teachers, with a sample of 137 teachers determined using the Krejcie and Morgan table through a proportional random sampling technique. Data were collected using a Likert scale questionnaire that was tested for validity and reliability. The results showed that the implementation of PMM reached 80.67% and teachers' pedagogical competence was 79.24%. There was a significant relationship between the implementation of PMM and teachers' pedagogical competence, with a calculated r value of 0.319 (greater than the r table value of 0.167) and a calculated t value of 3.911 (greater than the t table value of 1.977) at a 95% significance level. In conclusion, the implementation of PMM has a significant effect on teachers' pedagogical competence. It is recommended that school principals regularly conduct training, teachers actively develop competencies through PMM, the Education Office provide policy and infrastructure support, and conduct periodic monitoring and evaluation to optimize the implementation of PMM.